2009
DOI: 10.2746/042516409x368912
|View full text |Cite
|
Sign up to set email alerts
|

Clinical dental examinations of 357 donkeys in the UK. Part 1: Prevalence of dental disorders

Abstract: SummaryReasons for performing study: Dental disorders have a high prevalence in older donkeys and horses, but the nature and pathogenesis of many of these disorders have yet to be established. Objectives: The identification and determination of the prevalence of important dental disorders in different age groups in a large single population of donkeys, to establish a better understanding of the nature and pathogenesis of these disorders. Methods: A prospective cross-sectional study was performed on the donkey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(86 citation statements)
references
References 12 publications
7
75
4
Order By: Relevance
“…In previous studies, the age of the animals was categorised using different cut-off points where younger age groups were shown to have a significantly lower prevalence of dental disorders. Sharp enamel points, however, were found to be significantly higher in donkeys aged 0-10 years old in one study [2] and cheek teeth fractures did not differ significantly among age groups in another study [1]. The current study has also demonstrated a significant linear effect of age on the prevalence of no/mild dental disease where increasing age was associated with a decreasing number of horses assigned to this category [14,18].…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…In previous studies, the age of the animals was categorised using different cut-off points where younger age groups were shown to have a significantly lower prevalence of dental disorders. Sharp enamel points, however, were found to be significantly higher in donkeys aged 0-10 years old in one study [2] and cheek teeth fractures did not differ significantly among age groups in another study [1]. The current study has also demonstrated a significant linear effect of age on the prevalence of no/mild dental disease where increasing age was associated with a decreasing number of horses assigned to this category [14,18].…”
Section: Discussionsupporting
confidence: 53%
“…The effect of age on the prevalence of dental disorders has previously been reported [1,2,18,33,35]. In previous studies, the age of the animals was categorised using different cut-off points where younger age groups were shown to have a significantly lower prevalence of dental disorders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3. Smile mouth (SmM), an abnormality of the incisors whereby the occlusal surface of the incisors wears unevenly to a downwardly curved surface (Du Toit et al, 2009). The authors have, by extension, also included a dorsal curvature of the incisors in this category.…”
Section: Generalised Incisor Overgrowths (Gios) the Authorsmentioning
confidence: 99%